Comparison of the stability boundary and the frequency response stability condition in learning and repetitive control - Songschon, Szathys; Longman, Richard W. (Zielona Góra: Uniwersytet Zielonogórski)
In iterative learning control (ILC) and in repetitive control (RC) one is interested in convergence to zero tracking error as the repetitions of the command or the periods in the command progress. A condition based on steady state frequency response modeling is often used, but it does not represent the true stability boundary for convergence.
Keywords: iterative learning control; repetitive control; stability; monotonic convergence